Analysis of the Competitive Strength of PT Bank Central Asia Tbk (BCA) through the Product Development Strategy of BCA Digital - Oktaviyah, Nurafni; Akbar, Wina Ayudia (Universitas Negeri Makassar, 2024)
This study analyzes the competitive strength of PT Bank Central Asia Tbk (BCA) through its digital product development strategy, specifically the blu application developed by BCA Digital. A qualitative approach is used to gain a deeper understanding of how the development of the blu product has enhanced BCA's competitiveness in the banking industry. The data used in this study are secondary data derived from previously published scientific articles and journals, as well as observational results from various sources, including prior research, books, and relevant news. The main focus of this study is on the blu digital product innovation, which offers easy access to banking services through mobile devices. The findings indicate that the blu innovation not only increases convenience and efficiency for customers but also strengthens BCA's position as a leader in digital banking in Indonesia. This strategy enables BCA to effectively respond to changing trends and customer needs, thereby maintaining and enhancing its competitive advantage.Penelitian ini menganalisis kekuatan kompetitif PT Bank Central Asia Tbk (BCA) melalui strategi pengembangan produk digital, khususnya aplikasi blu yang dikembangkan oleh BCA Digital. Pendekatan kualitatif digunakan untuk memahami secara mendalam bagaimana pengembangan produk blu mampu meningkatkan daya saing BCA di industri perbankan. Data yang digunakan adalah data sekunder yang berasal dari artikel ilmiah dan jurnal yang telah dipublikasikan sebelumnya serta hasil observasi dari berbagai sumber, termasuk penelitian terdahulu, buku, dan berita terkait. Fokus utama dari penelitian ini adalah pada inovasi produk digital blu, yang menawarkan kemudahan akses layanan perbankan melalui perangkat gawai. Hasil penelitian menunjukkan bahwa inovasi blu tidak hanya meningkatkan kenyamanan dan efisiensi bagi nasabah, tetapi juga memperkuat posisi BCA sebagai pemimpin dalam perbankan digital di Indonesia. Strategi ini memungkinkan BCA untuk merespons perubahan tren dan kebutuhan nasabah secara efektif, sehingga mempertahankan dan meningkatkan keunggulan kompetitifnya.